Pengetahuan Berpengaruh Terhadap Kepatuhan Dalam Perawatan Kaki Pada Klien Diabetes Melitus Tipe II - Dian Hudiyawati; Sabila Rizki (Poltekkes Kemenkes Surakarta, 2018)
Background: An increasing number of people with diabetes mellitus will increase the risk of chronic complications, one of which is neuropathy. Diabetic neuropathy can cause disability and even death. Management of Diabetes Mellitus is intended to prevent the occurrence of complications by educating clients about foot care. it aims to improve the knowledge and adherence of people with diabetes mellitus. The purpose of this study was to determine the relationship of the knowledge level of foot care with adherence in performing foot care in patients with Type II Diabetes Mellitus. Research Methods. this study was quantitative research using descriptive-analytic method through a cross-sectional study approach. Data analysis used Chi-Square. This research questionnaire used Nottingham Assessment of Functional Footcare (NAFF) to measure knowledge Rnd Diabetic Foot Care Behavior (DFCB) to measure compliance. Results showed a significant relationship between the level of knowledge with patient compliance in performing foot care (p = 0.001). Conclusion, Based on these results can be concluded that people with diabetes mellitus who have good knowledge will tend to increase adherence in performing foot care.